Adsorption Behavior of Multi-Component BTEX on the Synthesized Green Adsorbents Derived from Abelmoschus esculentus L. Waste Residue - Isinkaralar, Kaan; Meruyert, Keikimanova (Springer Science and Business Media LLC, 2023)
Benzene, toluene, ethylbenzene, and xylene (BTEX) removal is one of the most common difficulties in air pollution control. They are emitted from several processes, prejudicial to the environment and humans. BTEX leads to various environmental risks, and there is a significant need for a creating process for the complete removal of BTEX from air streams. This study's objective is the multi-component adsorption of BTEX pollutants from an air stream, by synthesizing activated carbons (ACs) under several operations. A lignocellulosic waste biomass, Abelmoschus esculentus L. (AE), was utilized as the precursor for synthesizing activated carbons (AE-ACs), and their surface chemical characteristics were investigated. Optimization processes were examined, and the change in the surface area of AE-ACs was investigated as change of some variables results like activation agent, impregnation ratio, temperature, and activation time. The maximum surface area of 968 m2/g and total pore volume of 0.51 cm3/g were attained at 1:2 impregnation ratio, activation time of 110 min, and activation temperature of 800 °C, under N2 atmosphere. A mixture of BTEX pollutants was employed to consider the effect of humidity (0.5, 1, 1.5, and 2 wt%) and initial concentrations (from 5 to 300 mg/m3), using a contact time of 120 min at the temperature of 25 °C. Under the studied conditions, the multi-component and single-component BTEX adsorption capacities by HCl-activated carbon, AE-ACH, were specifically achieved to 6.86-51.36 mg/g and 22-93.62 mg/g, respectively. Overall, Abelmoschus esculentus L. was exploited for the synthesis of AE-ACH which was successfully utilized for efficient BTEX capture from a polluted air stream.
Keywords: Air Pollutants; Abelmoschus; Benzene Derivatives; Humans; Benzene; Environmental Pollutants; Adsorption; Xylenes; Toluene; 13. Climate action; 6. Clean water